A 500 pc volume-limited sample of hot subluminous stars: I. Space density, scale height, and population properties - Dawson, H.; Geier, S.; Heber, Ulrich; Pelisoli, I.; Dorsch, M.; Schaffenroth, V.; Reindl, N.; Culpan, R.; Pritzkuleit, M.; Vos, J.; Soemitro, A. A.; Roth, M. M.; et al. (Astronomy & Astrophysics, 2024)
We present the first volume-limited sample of spectroscopically confirmed hot subluminous stars out to 500 pc, defined using the accurate parallax measurements from the Gaia space mission data release 3 (DR3). The sample comprises a total of 397 members, with 305 (∼77%) identified as hot subdwarf stars, including 83 newly discovered systems. Of these, we observe that 178 (∼58%) are hydrogen-rich sdBs, 65 are sdOBs (∼21%), 32 are sdOs (∼11%), and 30 are He-sdO/Bs (∼10%). Among them, 48 (∼16%) exhibit an infrared excess in their spectral energy distribution fits, suggesting a composite binary system. The hot subdwarf population is estimated to be 90% complete, assuming that most missing systems are these composite binaries located within the main sequence (MS) in the Gaia colour-magnitude diagram. The remaining sources in the sample include cataclysmic variables, blue horizontal branch stars, hot white dwarfs, and MS stars. We derived the mid-plane density ρ0 and scale height hz for the non-composite hot subdwarf star population using a hyperbolic sechant profile (sech2). The best-fit values are ρ0 = 5.17 ± 0.33 A-10a7 stars pca3 and hz = 281 ± 62 pc. When accounting for the composite-colour hot subdwarfs and their estimated completeness, the mid-plane density increases to ρ0 = 6.15a 0.53+1.16 A10a stars pca3. This corrected space density is an order of magnitude lower than predicted by population synthesis studies, supporting previous observational estimates.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Binaries: general; Catalogs; Hertzsprunga Russell and Ca M diagrams; Stars: statistics; Subdwarfs

A hot subdwarf-white dwarf super-Chandrasekhar candidate supernova Ia progenitor - Pelisoli, Ingrid; Neunteufel, P.; Geier, S.; Kupfer, T.; Heber, Ulrich; Irrgang, Andreas; Schneider, David; Bastian, A.; Van Roestel, J.; Schaffenroth,; Barlow, B. N. (Nature Astronomy, 2021)
Supernovae Ia are bright explosive events that can be used to estimate cosmological distances, allowing us to study the expansion of the Universe. They are understood to result from a thermonuclear detonation in a white dwarf that formed from the exhausted core of a star more massive than the Sun. However, the possible progenitor channels leading to an explosion are a long-standing debate, limiting the precision and accuracy of supernovae Ia as distance indicators. Here we present HD 265435, a binary system with an orbital period of less than a hundred minutes that consists of a white dwarf and a hot subdwarf, which is a stripped core-helium-burning star. The total mass of the system is 1.65 +/- 0.25 solar masses, exceeding the Chandrasekhar limit (the maximum mass of a stable white dwarf). The system will merge owing to gravitational wave emission in 70 million years, likely triggering a supernova Ia event. We use this detection to place constraints on the contribution of hot subdwarf-white dwarf binaries to supernova Ia progenitors.
CRIS-Team WoS Importer:2021-07-23

A New Class of Roche Lobe-filling Hot Subdwarf Binaries - Kupfer, Thomas; Bauer, Evan; Burdge, Kevin; van Roestel, Jan; Bellm, Eric; Fuller, Jim; Hermes, JJ; Marsh, Thomas R.; Bildsten, Lars; Kulkarni, Shrinivas R; Phinney, E S; Prince, Thomas A; et al. (Astrophysical Journal Letters, 2020)
We present the discovery of the second binary with a Roche lobe-filling hot subdwarf transferring mass to a white dwarf (WD) companion. This 56 minute binary was discovered using data from the Zwicky Transient Facility. Spectroscopic observations reveal an He-sdOB star with an effective temperature ofT(eff) = 33,700 1000 K and a surface gravity of log(g) = 5.54 0.11. The GTC+HiPERCAM light curve is dominated by the ellipsoidal deformation of the He-sdOB star and shows an eclipse of the He-sdOB by an accretion disk as well as a weak eclipse of the WD. We infer a He-sdOB mass ofM(sdOB) = 0.41 0.04Mand a WD mass ofM(WD) = 0.68 0.05M. The weak eclipses imply a WD blackbody temperature of 63,000 10,000 K and a radiusR(WD) = 0.0148 0.0020Ras expected for a WD of such high temperature. The He-sdOB star is likely undergoing hydrogen shell burning and will continue transferring mass for 1 Myr at a rate of 10(-9)Myr(-1), which is consistent with the high WD temperature. The hot subdwarf will then turn into a WD and the system will merge in 30 Myr. We suggest that Galactic reddening could bias discoveries toward preferentially finding Roche lobe-filling systems during the short-lived shell-burning phase. Studies using reddening-corrected samples should reveal a large population of helium core-burning hot subdwarfs withT(eff) 25,000 K in binaries of 60-90 minutes with WDs. Though not yet in contact, these binaries would eventually come into contact through gravitational-wave emission and explode as a subluminous thermonuclear supernova or evolve into a massive single WD.
Keywords: B subdwarf stars; Stellar evolution; White dwarf stars; Compact binary stars; Stellar accretion

A quantitative in-depth analysis of the prototype sdB plus BD system SDSS J08205+0008 revisited in the Gaia era - Schaffenroth, V.; Casewell, S. L.; Schneider, David; Kilkenny, D.; Geier, S.; Heber, Ulrich; Irrgang, Andreas; Przybilla, N.; Marsh, T. R.; Littlefair, S. P.; Dhillon, V. S. (Monthly Notices of the Royal Astronomical Society, 2021)
Subdwarf B stars are core-helium-burning stars located on the extreme horizontal branch (EHB). Extensive mass loss on the red giant branch is necessary to form them. It has been proposed that substellar companions could lead to the required mass loss when they are engulfed in the envelope of the red giant star. J08205+0008 was the first example of a hot subdwarf star with a close, substellar companion candidate to be found. Here, we perform an in-depth re-analysis of this important system with much higher quality data allowing additional analysis methods. From the higher resolution spectra obtained with ESO-VLT/XSHOOTER, we derive the chemical abundances of the hot subdwarf as well as its rotational velocity. Using the Gaia parallax and a fit to the spectral energy distribution in the secondary eclipse, tight constraints to the radius of the hot subdwarf are derived. From a long-term photometric campaign, we detected a significant period decrease of -3.2(8) x 10(-12) dd(-1). This can be explained by the non-synchronized hot subdwarf star being spun up by tidal interactions forcing it to become synchronized. From the rate of period decrease we could derive the synchronization time-scale to be 4 Myr, much smaller than the lifetime on EHB. By combining all different methods, we could constrain the hot subdwarf to a mass of 0.39-0.50 M-circle dot and a radius of R-sdB = 0.194 +/- 0.008 R-circle dot, and the companion to 0.061-0.071 M-circle dot with a radius of R-comp = 0.092 +/- 0.005 R-circle dot, below the hydrogen-burning limit. We therefore confirm that the companion is most likely a massive brown dwarf.
CRIS-Team WoS Importer:2021-03-26

Discovery of a Double-detonation Thermonuclear Supernova Progenitor - Kupfer, Thomas; Bauer, Evan B.; Van Roestel, Jan; Bellm, Eric C.; Bildsten, Lars; Fuller, Jim; Prince, Thomas A.; Heber, Ulrich; Geier, Stephan; Green, Matthew J.; Kulkarni, Shrinivas R.; Bloemen, Steven; et al. (Astrophysical Journal Letters, 2022)
We present the discovery of a new double-detonation progenitor system consisting of a hot subdwarf B (sdB) binary with a white dwarf companion with a P (orb) = 76.34179(2) minutes orbital period. Spectroscopic observations are consistent with an sdB star during helium core burning residing on the extreme horizontal branch. Chimera light curves are dominated by ellipsoidal deformation of the sdB star and a weak eclipse of the companion white dwarf. Combining spectroscopic and light curve fits, we find a low-mass sdB star, M (sdB) = 0.383 +/- 0.028 M (circle dot) with a massive white dwarf companion, M (WD) = 0.725 +/- 0.026 M (circle dot). From the eclipses we find a blackbody temperature for the white dwarf of 26,800 K resulting in a cooling age of approximate to 25 Myr whereas our MESA model predicts an sdB age of approximate to 170 Myr. We conclude that the sdB formed first through stable mass transfer followed by a common envelope which led to the formation of the white dwarf companion approximate to 25 Myr ago. Using the MESA stellar evolutionary code we find that the sdB star will start mass transfer in approximate to 6 Myr and in approximate to 60 Myr the white dwarf will reach a total mass of 0.92 M (circle dot) with a thick helium layer of 0.17 M (circle dot). This will lead to a detonation that will likely destroy the white dwarf in a peculiar thermonuclear supernova. PTF1 J2238+7430 is only the second confirmed candidate for a double-detonation thermonuclear supernova. Using both systems we estimate that at least approximate to 1% of white dwarf thermonuclear supernovae originate from sdB+WD binaries with thick helium layers, consistent with the small number of observed peculiar thermonuclear explosions.
CRIS-Team WoS Importer:2022-02-04

EVR-CB-004: An Inflated Hot Subdwarf O Star plus Unseen WD Companion in a Compact Binary Discovered with the Evryscope - Ratzloff, Jeffrey K.; Kupfer, Thomas; Barlow, Brad N.; Schneider, David; Marsh, Thomas R.; Heber, Ulrich; Corcoran, Kyle A.; Bauer, Evan; Hämmerich, Steven; Corbett, Henry T.; Glazier, Amy; Howard, Ward S.; et al. (Astrophysical Journal, 2020)
We present the discovery of EVR-CB-004, a close binary with a remnant stellar core and an unseen white dwarf (WD) companion. The analysis in this work reveals that the primary is potentially an inflated hot subdwarf (sdO) and more likely is a rarer post-blue horizontal branch (post-BHB) star. Post-BHBs are the short-lived shell-burning final stage of a blue horizontal star or hot subdwarf before transitioning to a WD. This object was discovered using Evryscope photometric data in a southern all-sky hot subdwarf variability survey. The photometric light curve for EVR-CB-004 shows multicomponent variability from ellipsoidal deformation of the primary and Doppler boosting, as well as gravitational limb darkening. The binary EVR-CB-004 is one of just a handful of known systems and has a long period (6.08426 hr) and large-amplitude ellipsoidal modulation (16.0% change in brightness from maximum to minimum) for these extremely close binary systems, while the properties of the primary make it a truly unique system. It also shows a peculiar low-amplitude (less than 1%) sinusoidal light-curve variation with a period that is a 1/3 resonance of the binary period. We tentatively identify this additional variation source as a tidally induced resonant pulsation, and we suggest follow-up observations that could verify this interpretation. From the evolutionary state of the system, its components, and its mass fraction, EVR-CB-004 is a strong merger candidate to form a single high-mass (1.2M) WD. It offers a glimpse into a brief phase of remnant core evolution and secondary variation not seen before in a compact binary.
CRIS-Team WoS Importer:2020-10-30

NLTE spectroscopic analysis of the He-3 anomaly in subluminous B-type stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Heber, Ulrich; Nieva, M. F.; Przybilla, N. (Astronomy & Astrophysics, 2018)
Several B-type main-sequence stars show chemical peculiarities. A particularly striking class are the He-3 stars, which exhibit a remarkable enrichment of He-3 with respect to He-4. This isotopic anomaly has also been found in blue horizontal branch (BHB) and subdwarf B (sdB) stars, which are helium-core burning stars of the extreme horizontal branch. Recent surveys uncovered 11 He-3 sdBs. The He-3 anomaly is not due to thermonuclear processes, but caused by atomic diffusion in the stellar atmosphere. Using a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars, we analyzed high-quality spectra of two known He-3 BHBs and nine known He-3 sdBs to determine their isotopic helium abundances and He-4/He-3 abundance ratios. We redetermined their atmospheric parameters and analyzed selected He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which are very sensitive to He-4/He-3. Most of the He-3 sdBs cluster in a narrow temperature strip between 26 000K and 30 000K and are helium deficient in accordance with previous LTE analyses. BD + 48 degrees 2721 is reclassified as a BHB star because of its low temperature (T-eff = 20 700 K). Whereas He-4 is almost absent (He-4/He-3 < 0.25) in most of the known He-3 stars, other sample stars show abundance ratios up to He-4/He-3 similar to 2.51. A search for He-3 stars among 26 candidate sdBs from the ESO SPY survey led to the discovery of two new He-3 sdB stars (HE 0929-0424 and HE 1047-0436). The observed helium line profiles of all BHBs and of three sdBs are not matched by chemically homogeneous atmospheres, but hint at vertical helium stratification. This phenomenon has been seen in other peculiar B-type stars, but is found for the first time for sdBs. We estimate helium to increase from the outer to the inner atmosphere by factors ranging from 1.4 (SB 290) up to 8.0 (BD + 48 degrees 2721).
Keywords: stars: chemically peculiar; stars: atmospheres; stars: fundamental parameters; stars: abundances; subdwarfs; stars: horizontal-branch

On the He-3 anomaly in hot subdwarf B stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Nieva, M. F.; Przybilla, Norbert (SCIENDO, 2017)
Decades ago, He-3 isotope enrichment in helium-weak B-type main-sequence, in blue horizontal branch and in hot subdwarf B (sdB) stars, i.e., helium-core burning stars of the extreme horizontal branch, were discovered. Diffusion processes in the atmosphere of these stars lead to the observed abundance anomalies. Quantitative spectral analyses of high-resolution spectra to derive photospheric isotopic helium abundance ratios for known He-3 sdBs have not been performed yet. We present preliminary results of high-resolution and high S/N spectra to determine the He-3 and He-4 abundances of nine known He-3 sdBs. We used a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars investigating multiple He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which show the strongest isotopic shifts in the optical spectral range. We also report the discovery of four new He-3 sdBs from the ESO Supernova Progenitor survey. Most of the He-3 sdBs cluster in a narrow temperature strip between similar to 26000 K and similar to 30000 K and have almost no atmospheric He-4 at all. Interestingly, three He-3 sdBs show evidence for vertical helium stratification.
Keywords: Stars: chemically peculiar; Stars: atmospheres; Stars: fundamental parameters; Stars: abundances; subdwarfs; Stars: horizontal-branch

Runaway blue main-sequence stars at high Galactic latitudes: Target selection with Gaia and spectroscopic identification - Raddi, Roberto; Irrgang, Andreas; Heber, Ulrich; Schneider, David; Kreuzer, Simon (Astronomy & Astrophysics, 2021)
Context. The ESA Gaia mission is a remarkable tool for stellar population analysis through its accurate Hertzsprung-Russell diagram. Its precise astrometry has propelled detailed kinematic studies of the Milky Way and the identification of high-velocity outliers. Aims. Motivated by the historical identification of runaway main-sequence (MS) stars of an early spectral type at high Galactic latitudes, we test the capability of Gaia at identifying new such stars. Methods. We selected ≃2300 sources with Gaia magnitudes of GBP-GRP ≤ 0.05, which are compatible with the colors of lowextinction MS stars that are earlier than a mid-A spectral type, and obtained low-resolution optical spectroscopy for 48 such stars. By performing detailed photometric and spectroscopic analyses, we derived their atmospheric and physical parameters (effective temperature, surface gravity, radial velocity, interstellar reddening, spectrophotometric distance, mass, radius, luminosity, and age). The comparison between spectrophotometric and parallax-based distances enabled us to disentangle the MS candidates from older blue horizontal branch (BHB) candidates. Results.We identify 12 runaway MS candidates, with masses between 2 and 6 M⊙. Their trajectories were traced back to the Galactic disk in order to identify their most recent Galactic plane crossings and the corresponding flight times. All 12 candidates are ejected from the Galactic disk within 2 to 16.5 kpc from the Galactic center and possess flight times that are shorter than their evolutionary ages, which is compatible with a runaway hypothesis. Three MS candidates have ejection velocities exceeding 450 km s-1, thus, they appear to challenge the canonical ejection scenarios for late B-type stars. The fastest star of our sample also has a non-negligible Galactic escape probability if its MS nature can be confirmed.We identify 27 BHB candidates, and the two hottest stars in our sample are rare low-mass stars of late O- A nd early B-types, evolving towards the white dwarf cooling sequence. Conclusions. The combination of Gaia parallaxes and proper motions can lead to the efficient selection of runaway blue MS candidates up to 10 kpc away from the Sun. High resolution spectra are needed to confirm the MS status, via precise measurements of projected rotational velocities and chemical compositions.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: Early-type; Stars: Fundamental parameters; Stars: Horizontal-branch; Stars: Kinematics and dynamics

The MUCHFUSS photometric campaign - Schaffenroth, Veronika; Geier, S.; Heber, Ulrich; Gerber, Raoul; Schneider, David; Ziegerer, Eva; Cordes, O. (Astronomy & Astrophysics, 2018)
Hot subdwarfs (sdO/Bs) are the helium-burning cores of red giants, which have lost almost all of their hydrogen envelope. This mass loss is often triggered by common envelope interactions with close stellar or even substellar companions. Cool companions like late-type stars or brown dwarfs are detectable via characteristic light-curve variations like reflection effects and often also eclipses. To search for such objects, we obtained multi-band light curves of 26 close sdO/B binary candidates from the MUCHFUSS project with the BUSCA instrument. We discovered a new eclipsing reflection effect system (P = 0 : 168938 d) with a low-mass M dwarf companion (0.116 M-circle dot). Three more reflection effect binaries found in the course of the campaign have already been published; two of them are eclipsing systems, and in one system only showing the reflection effect but no eclipses, the sdB primary is found to be pulsating. Amongst the targets without reflection effect a new long-period sdB pulsator was discovered and irregular light variations were found in two sdO stars. The found light variations allowed us to constrain the fraction of reflection effect binaries and the substellar companion fraction around sdB stars. The minimum fraction of reflection effect systems amongst the close sdB binaries might be greater than 15% and the fraction of close substellar companions in sdB binaries may be as high as 8 .0%. This would result in a close substellar companion fraction to sdB stars of about 3%. This fraction is much higher than the fraction of brown dwarfs around possible progenitor systems, which are solar-type stars with substellar companions around 1AU, as well as close binary white dwarfs with brown dwarf companions. This might suggest that common envelope interactions with substellar objects are preferentially followed by a hot subdwarf phase.
Keywords: subdwarfs; binaries: eclipsing; binaries: spectroscopic; brown dwarfs; stars: fundamental parameters